2014
DOI: 10.1111/jfq.12081
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Xylanase, Ascorbic and Citric Acid in Regulating the Quality of Bread Made From Organically Grown Spelt Cultivars

Abstract: The present study was aimed at improving bread-making performance of two spelt cultivars from organic production differing in dough rheological properties. For this purpose, a small composite design was employed to study the combined effect of xylanase (XYL), ascorbic (ASC) and citric (CIT) acid on bread characteristics and, finally, to optimize their doses. In both cultivars, XYL exerted improving effects on specific volume and crumb firmness. In stronger spelt cultivar, there was a significant ASC/XYL synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The results in this study are comparable with the results of Filipcev et al (12), who reported a positive effect of xylanase on the loaf volume of bread. By contrast, the quadratic coefficient (β 22 = −034) of Xyl revealed a negative effect on the specific volume of bread.…”
Section: )supporting
confidence: 95%
See 2 more Smart Citations
“…The results in this study are comparable with the results of Filipcev et al (12), who reported a positive effect of xylanase on the loaf volume of bread. By contrast, the quadratic coefficient (β 22 = −034) of Xyl revealed a negative effect on the specific volume of bread.…”
Section: )supporting
confidence: 95%
“…Xylanase hydrolyzes arabinoxylans that interfere with the formation of a gluten network (10). Combinations of chemical oxidizing agents and crosslinking enzymes have frequently been used to improve the quality of flour and the end product (4,(11)(12)(13). Simurina et al investigated the effect of a combination of TGase and L-AA on substandard quality wheat flour and observed an improvement in dough properties as well as the quality of bread prepared from substandard wheat flour compared to dough and bread without these additives.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…No technologies involving genetically modified organisms can be utilized to increase the yield in enzyme production or to make the enzyme specificity better suited for the desired application. Some additives or enzymes with a broader specificity are allowed in the organic bakery market, such as lecithin and classical lipases or xylanases (6). However, no suitable alternative currently exists to retard staling using nonessential ingredients or to improve dough stability in organic bread.…”
Section: Demand For Healthier or Organic Productsmentioning
confidence: 99%
“…In modern breadmaking, dough additives have been used to improve dough handling properties by overcoming some deficiencies in the bread‐making quality of the wheat gluten (Filipčev et al . ). L‐ascorbic acid (E300), bromate, calcium iodate and azodicarbonamide are the most common oxidizing agents used to strengthen the structure of dough through oxidation of thiol groups into disulfide bridges (Tsen ; Horvat et al .…”
Section: Introductionmentioning
confidence: 97%